FEATURES OF ADVANCE REGENERATION OF TREE SPECIES IN DRY MAPLE-LIME OAK FOREST IN THE LEFT-BANK FOREST-STEPPE - Rumyantsev, M. G. (Forestry and Forest Melioration, 2018)
Introduction One of the main aspects of forest management is the study of forests natural regeneration and factors affecting the emergence and development of young seedling and advance growth. The problem of renewal of oak stands remains topical issue for today as recently few works are devoted to the study of this question. Some researches are devoted to studying of advance regeneration in the conditions of fresh oak forests of the Left-bank Forest-steppe, but in the conditions of a dry maple-lime oak forest this question isn’t studied at all. Therefore the detection of features of distribution of tree species advance growth, the analysis of its qualitative state will allow predicting further existence and development of forest stands in the conditions of a dry maple-lime oak forest coenosis of the region. Materials and Methods During the research, the method of accounting for natural regeneration developed in URIFFM was used. The advance growth was distributed by species, groups of height, age and viability state. 200 discounting areas (10 sq. m each) on 8 sample plots were established. For assessment of natural regeneration success a scale developed in URIFFM was applied with recalculation of small and medium advance growth into the large one. Results The conducted researches allowed defining that the total of regeneration under the canopy of natural oak stands in the conditions of a dry maple-lime oak forest fluctuates over a wide range - from 3.90 to 20.50 thousands units?ha-1. As a part of advance growth, 7 tree species are revealed; advance growth of a Norway maple is the most presented in a quantitative ratio (from 2.4 to 67.2 %), common ash (4.4-55.7 %) and field maple (7.7-52.8 %) are less presented. On separate plots the share of English oak reaches from 43.8 to 50.7 %, on other plots it is from 4.4 to 7.8 %. Participation of wych elm doesn’t exceed 10 % of total and regeneration of other species, small-leafed linden and aspen, is revealed to be occasional and is within several sample plots in insignificant quantity. The successfulness of advance regeneration of principal forest forming species - oak and ash -is characterized as poor or insufficient and only at separate sites as good. The most number of seedlings of principal species is observed in plantations of 80-121 years old, in which the participation of oak is 8 units, and ash is 1-3 units in the parent stand composition. Advance growth of an oak is placed on the area unevenly, and young seedlings of an oak are characterized by uniform placement on the area. Advance growth of maples is placed on the area evenly, an ash, elm and linden - unevenly. Conclusions In the conditions of a dry maple-lime oak forest, after productive year, under canopy of oak forest stands, there is enough regeneration of a oak (from 5.60 to 10.40 thousand units?ha-1) with uniform placement on the area even without carrying out actions for assistance to regeneration. Therefore, on such sites, it is necessary to carry out a complex of silvicultural actions for natural regeneration of the valuable oak forests of a seed origin (selective and shelterwood principal felling, action for natural regeneration assistance, tending an advance growth of valuable species in dense groups of natural regeneration), considering thus, first of all, frequency of fructification of an oak.